2018
DOI: 10.1111/bcp.13607
|View full text |Cite
|
Sign up to set email alerts
|

Hospital readmissions, mortality and potentially inappropriate prescribing: a retrospective study of older adults discharged from hospital

Abstract: Using version 2 of the STOPP/START criteria, the presence of PIMs and/or PPOs in older adults discharged from hospital is significantly associated with repeated hospital admissions and mortality respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
66
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 50 publications
8
66
7
2
Order By: Relevance
“…At odds with some previous studies 25,34 , PIMs and PPOs were not significantly associated with all-cause mortality in both discharge settings. However, the study of Wauters et al included community-dwelling subjects with better health and functional status compared with the patients in our study 34 , whereas Counter et al retrospectively evaluated 259 hospital-discharged patients with scant clinical data and no CGA 25 . In a population of older hospital-discharged patients with high short-term mortality, it is very likely that the burden of comorbidities and poor health status may reduce the impact of inappropriate prescribing on hard outcomes such as mortality and unplanned readmissions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…At odds with some previous studies 25,34 , PIMs and PPOs were not significantly associated with all-cause mortality in both discharge settings. However, the study of Wauters et al included community-dwelling subjects with better health and functional status compared with the patients in our study 34 , whereas Counter et al retrospectively evaluated 259 hospital-discharged patients with scant clinical data and no CGA 25 . In a population of older hospital-discharged patients with high short-term mortality, it is very likely that the burden of comorbidities and poor health status may reduce the impact of inappropriate prescribing on hard outcomes such as mortality and unplanned readmissions.…”
Section: Discussioncontrasting
confidence: 99%
“…The main findings of this study were: 1) PIMs, PPOs and number of drugs at discharge were not significantly associated with all-cause mortality in the overall study sample and in each discharge setting; 2) a higher number of PIMs was significantly associated with unplanned hospital readmission in the overall study sample (OR 1. 23 25 . In a prospective study on 1,753 community-dwellers, the prevalence of PIMs and PPOs were 57% and 41.8%, respectively, and higher rates of emergency department visits were observed in those with at least one PIM, or with two or more PPOs 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,15,20,22 Our study found much higher rates of deprescribing than those quoted in the literature. 5,15,20,22 Our study found much higher rates of deprescribing than those quoted in the literature.…”
Section: Discussioncontrasting
confidence: 51%
“…Rates of in-hospital deprescribing vary widely and range from a complete lack of deprescribing to 1 in 5 patients having a PIM stopped or tapered at discharge. 5,15,20,22 Our study found much higher rates of deprescribing than those quoted in the literature. All sites had a strong baseline culture of deprescribing and were highly sensitized to the issues of polypharmacy and ADEs.…”
Section: Discussioncontrasting
confidence: 51%